Losses, dividend reductions, and market reaction associated with past earnings and dividends patterns - Theodoulou, Giorgos; Lambertides, Neophytos; Charitou, Andreas (My University, 2011)
This paper examines investors' reactions to dividend reductions or omissions conditional on past earnings and dividend patterns for a sample of eighty-two U.S. firms that incurred an annual loss. We document that the market reaction for firms with long patterns of past earnings and dividend payouts is significantly more negative than for firms with lessestablished past earnings and dividends records. Our results can be explained by the following line of reasoning. First, consistent with DeAngelo, DeAngelo, and Skinner (1992), a loss following a long stream of earnings and dividend payments represents an unreliable indicator of future earnings. Thus, established firms have higher loss reliability than less-established firms. Second, because current earnings and dividend policy are a substitute source of means of forecasting future earnings, lower loss reliability increases the information content of dividend reductions. Therefore, given the presence of a loss, the longer the stream of prior earnings and dividend payments, (1) the lower the loss reliability and (2) the more reliably dividend cuts are perceived as an indication that earnings difficulties will persist in the future
Keywords: Dividend Announcements; Dividend Omissions; Dividend Reductions; Earnings; Event Study; Losses; Patterns